Социология интимности: секс, эротика и любовь в постмодерной деконструкции - Танчер, В. (Социология: теория, методы, маркетинг, 2001)
Intimacies taking place in lives of modern people mostly attract attention of sociologists in situations when the post-modern priorities are changing. We can see some sociologization of intimacies, deconstruction of their components: sexual relationships, eroticism and love, in which eroticism becomes self-sufficient and the whole sphere can be described as more democratic. Sexuality becomes the field, where people can realize themselves, as well as the main direction of their emancipation.